(Li, Na, K)NbO3-based multilayer piezoceramic with Ag/Pd inner electrodes. (30th July 2020) - Hatano, Keiichi; Watanabe, Gouki; Kishimoto, Sumiaki; Sasaki, Nobuhiro
Abstract: Lead-free (Li, Na, K)NbO3 -based multilayer piezoceramics with Ag/Pd inner electrodes were fabricated. Each multilayer piezoceramic comprised 20 layers, and each layer had a thickness of 13 μ m. These multilayer piezoceramics succeeded in driving a high electric field of 16 kV mm −1, while producing a strain of 0.24%. The microstructure was investigated using scanning electron microscopy and scanning transmission electron microscopy. It was found that the grain size was 400 nm and the ceramic layer had high densification. The elemental Ag also diffused uniformly throughout the ceramic layers, as observed by an energy dispersive X-ray spectrometer. This outstanding thin-layer stacking design of the lead-free piezoceramic could result in a displacement property exceeding that of a Pb(Zr, Ti)O3 -based multilayer piezoceramic. However, the electric resistance was low (4.2 × 10 12 Ω ‧ cm at 100 °C) compared with that of multilayered Pb(Zr, Ti)O3 (1.9 × 10 13 Ω ‧ cm at 100 °C). Therefore, the electric resistance must be improved before replacing lead-containing piezoceramics.